Analisis Dan Perancangan Data Warehouse Pada PT Pelita Tatamas Jaya - Huda, Choirul; Ranope, Jumas; Lumenta, Marly; Kevin, Kevin (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this research is to assist in providing information to support decision-making processes in sales, purchasing and inventory control at PT Tatamas Pelita Jaya. With the support of data warehouse, business leaders can be more helpful in making decisions more quickly and precisely. Research methodology includes analysis of current systems, library research, designing a data warehousing schema using bintang. The result of this research is the availability of a data warehouse that can generate information quickly and precisely, thus helping the company in making decisions. The conclusion of this research is the application of data warehouse can be a media aide related parties on PT Tatamas Pelita Jaya in decision making.